Delirium due to hip fracture is associated with activated immune-inflammatory pathways and a reduction in negative immunoregulatory mechanisms - Paul Thisayakorn; Yanin Thipakorn; Saran Tantavisut; Sunee Sirivichayakul; Michael Maes (BMC Psychiatry, 2022)
Abstract Background The objectives of this study were to delineate whether delirium in older adults is associated with activation of the immune-inflammatory response system (IRS) as indicated by activation of M1, T helper (Th)1, and Th17 profiles, and/or by reduced activities of the compensatory immunoregulatory system (CIRS), including Th2 and T regulatory profiles. Methods We recruited 65 older adult patients with a low energy impact hip fracture who underwent hip fracture operation. The CAM-ICU and the Delirium Rating Scale, Revised-98-Thai version (DRS-R-98) were assessed pre-operatively and 1, 2 and 3 days after surgery. Blood samples (day 1 and 2) post-surgery were assayed for cytokines/chemokines using a MultiPlex assay and the neutrophil/lymphocyte ratio. Results We found that delirium and/or the DRS-R-98 score were associated with IRS activation as indicated by activated M1, Th1, Th17 and T cell growth profiles and by attenuated CIRS functions. The most important IRS biomarkers were CXCL8, interleukin (IL)-6, and tumor necrosis factor-α, and the most important CIRS biomarkers were IL-4 and soluble IL-1 receptor antagonist. We found that 42.5% of the variance in the actual changes in the DRS-R-98 score (averaged from day 1 to day 3) was explained by T cell growth factors, baseline DRS-R-98 scores and age. An increase in the NLR reflects overall IRS, M1, Th1, Th17, and Th2 activation. Conclusions Post-hip surgery delirium is associated with activated IRS pathways and appears especially in patients with lowered CIRS functions.